1997
DOI: 10.1016/s0735-1097(96)00531-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Early and Late Mortality in Men and Women After Isolated Coronary Artery Bypass Graft Surgery in Stockholm, Sweden, 1980 to 1989

Abstract: The results suggest that men and women run similar risks of early and late mortality after CABG when patient characteristics are taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 15 publications
1
57
1
Order By: Relevance
“…Although long-term outcomes with CABG in women are similar to or even better than those in men, women have higher rates of periprocedural morbidity and mortality. [1133][1134][1135][1136][1137][1138][1139] Several hypotheses have been suggested to explain this increased morbidity and mortality, including older age at presentation, more frequent need for urgent revascularization, more comorbid conditions, smaller body surface area and coronary arterial dimensions, and increased risk of bleeding. The fact that women on average are older than men at the time of CABG is thought, at least in part, to be due to the loss of the protective effects of estrogen with menopause.…”
Section: Womenmentioning
confidence: 99%
“…Although long-term outcomes with CABG in women are similar to or even better than those in men, women have higher rates of periprocedural morbidity and mortality. [1133][1134][1135][1136][1137][1138][1139] Several hypotheses have been suggested to explain this increased morbidity and mortality, including older age at presentation, more frequent need for urgent revascularization, more comorbid conditions, smaller body surface area and coronary arterial dimensions, and increased risk of bleeding. The fact that women on average are older than men at the time of CABG is thought, at least in part, to be due to the loss of the protective effects of estrogen with menopause.…”
Section: Womenmentioning
confidence: 99%
“…[419][420][421][422][423] However, the weight of evidence indicates that short-term mortality is higher in women. The most recent data from the STS National Cardiac Surgery Database for 2002 indicate an operative mortality of 3.54% in women compared with 2.15% in men.…”
Section: -415mentioning
confidence: 99%
“…379,422,[428][429][430][431] In some studies, women had even better long-term survival than men after adjusting for risk factors. 379,420 The reasons for improved longterm, but not short-term, survival are speculative.…”
Section: Long-term Mortalitymentioning
confidence: 99%
“…16 It has been suggested that complete revascularization, use of arterial grafts and the off-pump technique might decrease the disparity in mortality between female and male patients. [16][17][18] However, evidence still indicates that short-term mortality is higher in females than in males. 19 There have been no reports with regard to gender differences in clinical and angiographic outcomes after CABG from Japanese institutes.…”
mentioning
confidence: 99%